2014
DOI: 10.1094/cchem-03-13-0056-r
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bioprocessing on the Phenolic Acid Composition and Antioxidant Activity of Wheat Bran

Abstract: Cereal Chem. 91(3):255-261In the present study, bioprocessing with eight microbial strains including Bacillus species, yeasts, and filamentous fungi was evaluated for its potential to improve the phenolic acid composition and antioxidant activity of wheat bran. The soluble free and soluble conjugated fractions of ethanolic extracts of the treated bran samples were compared for their total phenolic contents, phenolic acid composition, and in vitro antioxidant activities. In general, total phenolic content in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
6
23
0
Order By: Relevance
“…Oat ( Avena sativa L.), even if consumed in lower quantities, has an increasing production trend (>25 million tons in 2017) [1] due to its recognition as a healthy food with high bioactive content [2]. Wheat and oat whole grains, and specifically their outer parts, are considered rich sources of phenolic compounds with significant antioxidant activity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Oat ( Avena sativa L.), even if consumed in lower quantities, has an increasing production trend (>25 million tons in 2017) [1] due to its recognition as a healthy food with high bioactive content [2]. Wheat and oat whole grains, and specifically their outer parts, are considered rich sources of phenolic compounds with significant antioxidant activity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Wheat bran contains a vast variety of phenolic acids, including ferulic acid, vanillic acid, coumaric acid, caffeic acid and chlorogenic acid . The effectiveness and bioavailability of these bound phenolic acids are quite limited (Zhang et al, 2014). The health benefits of phenolic acids have significant implications for the improvement of food quality, particularly through applications in functional foods and nutraceuticals (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although a few reports have indicated that fermentation by Aspergillus niger can release bound phenolic acids in wheat bran, the effects of fermentation by Aspergillus oryzae and Aspergillus awamori have not yet been reported (Hegde et al, 2006;Zhang et al, 2014). Different species have different fermentation properties, which will lead to different results in the release of bound phenolic acids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations